BIOLOGICS (BIOLOGICAL AGENTS): A NEW APPROACH IN THE TREATMENT OF PSORIASIS - Singh Satyapal; Js, Tripathi; Np, Rai (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Psoriasis is a chronic inflammatory and multifactorial systemic disorder with predominant manifestation over the skin and/or joints resulting from interactions between genetic pre-disposition and triggering environmental factors. Due to its systemic nature, patients exhibit a broad spectrum of symptoms that vary in severity. Although many patients, particularly those with the limited form of the disease, may be treated with topical therapy, those with extensive (moderate to severe) psoriasis eventually require phototherapy, systemic, or biologic therapy to adequately suppress the systemic, immunopathogenic process. Biological agents (biologics or biologicals) are a set of different engineered proteins. These are immunosuppressive agents, designed to selectively interfere with the immune mechanisms that induce psoriasis. Their use is restricted to the treatment of moderate to severe psoriasis, which has failed to respond to systemic therapies (and/or phototherapy) or where such treatments are contra-indicated or not tolerated. Biologics are becoming increasingly useful for the treatment of many skin diseases including psoriasis, particularly as alternatives for patients who have failed to tolerate or respond to conventional systemic therapies or where non-biologic systemic agents are unsuitable due to the presence of comorbidities. Biological therapies provide a targeted approach to treatment through interaction with specific components of the underlying immune and inflammatory disease processes. Keywords: Immunopathogenesis, Biologicals, Psoriasis, Quality of life, Psoriasis area and severity index, Dermatology life quality index.